2019
DOI: 10.1038/s41467-019-12417-w
|View full text |Cite
|
Sign up to set email alerts
|

Detection of spacer precursors formed in vivo during primed CRISPR adaptation

Abstract: Type I CRISPR-Cas loci provide prokaryotes with a nucleic-acid-based adaptive immunity against foreign DNA. Immunity involves adaptation, the integration of ~30-bp DNA fragments, termed prespacers, into the CRISPR array as spacers, and interference, the targeted degradation of DNA containing a protospacer. Interference-driven DNA degradation can be coupled with primed adaptation, in which spacers are acquired from DNA surrounding the targeted protospacer. Here we develop a method for strand-specific, high-thro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 38 publications
8
54
0
Order By: Relevance
“…S6). The result is an asymmetric intermediate, which is consistent with recent evidence that in vivo, spacer precursors detected during primed adaptation in both type I-E and type I-F systems share an asymmetrical structure characterized by a blunt non-PAM end and a 3Ј overhang at the PAM end (45).…”
Section: Editors' Pick: Prespacer Processing In E Colisupporting
confidence: 89%
“…S6). The result is an asymmetric intermediate, which is consistent with recent evidence that in vivo, spacer precursors detected during primed adaptation in both type I-E and type I-F systems share an asymmetrical structure characterized by a blunt non-PAM end and a 3Ј overhang at the PAM end (45).…”
Section: Editors' Pick: Prespacer Processing In E Colisupporting
confidence: 89%
“…Most likely, the CRISPR system was unable to eliminate the prophage from the genome, followed by primed adaptation of additional spacers from locations in the prophage vicinity. Interestingly, as priming is enhanced by CRISPR interference (14,36,37), it is striking that no apparent DNA damage was incurred. For M. elsdenii we found that all STS protospacers are on the same strand with an orientation bias characteristic of primed adaptation (14).…”
Section: Amplified Self-targeting In Prophages Regionsmentioning
confidence: 99%
“…The presence of consensus PAM sequence (AAG/CTT) increased the acquisition efficiency of prespacers ∼5-fold and ensured specific orientation of integration with the PAM-derived G/C immediately following the first repeat [57]. We developed a method for strand-specific HTS of short DNA fragments generated in vivo that we called FragSeq and that allowed us to detect prespacers in E. coli cells undergoing primed CRISPR adaptation ( Figure 5B) [79]. The method uses protocols that avoid the loss of short fragments during purification of DNA from cell lysates ( phenol-chloroform DNA purification) and size selection of spacer-sized fragments prior to [79] and primer extension [63].…”
Section: Detection Of Spacer Precursors In Vivomentioning
confidence: 99%
“…We developed a method for strand-specific HTS of short DNA fragments generated in vivo that we called FragSeq and that allowed us to detect prespacers in E. coli cells undergoing primed CRISPR adaptation ( Figure 5B) [79]. The method uses protocols that avoid the loss of short fragments during purification of DNA from cell lysates ( phenol-chloroform DNA purification) and size selection of spacer-sized fragments prior to [79] and primer extension [63]. A prespacer (blue and red rectangles) in DNA (blue and red lines) is bound by the Cas1-Cas2 complex (light green).…”
Section: Detection Of Spacer Precursors In Vivomentioning
confidence: 99%
See 1 more Smart Citation